The influence of diet on isotope ratio mass spectrometry values - Green, G.; Aguilera, R.; Ahrens, B.; Starcevic, B.; Kurtzman, F.; Su, J.; Catlin, D. (Clinical Journal of Sport Medicine, 2009)
Objectives: Athletes have increasingly used testosterone (T) and other endogenous anabolic steroids that cannot be detected by conventional gas chromatography-mass spectrometry. This led to gas chromatography-combustion-isotope ratio mass spectrometry (GC/C/IRMS), which measures the relative amount of 13C in urinary steroids. Because exogenous testosterone is relatively low in 13C content, this study will determine if consuming a diet low in 13C plants, such as soy, can be confused with a GC/C/IRMS-positive test for exogenous testosterone.